Machines that can see. (Economist, 2009)
The article focuses on advances in computer vision research. Omrom Corp., a developer of robotics software, has produced software capable of recognizing and classifying digital images of facial expressions. Scientists have designed software which can analyze the authenticity of facial expressions by human, which is being used by corporations in marketing research.